2010
DOI: 10.1002/ptr.3164
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms of vasorelaxation for 5,7‐dimethoxyflavone from Kaempferia parviflora in the rat aorta

Abstract: The present study investigated the vascular effects of 5,7-dimethoxyflavone (DMF), isolated from the rhizomes of Kaempferia parviflora (KP), on rat isolated aortic rings and its possible mechanisms. DMF (1-100 μM) caused concentration-dependent relaxations in aortic rings precontracted with methoxamine. This effect was significantly reduced by removal of the endothelium, and after pretreatment with N(G)-nitro-L-arginine methyl ester (L-NAME, 300 μM), indomethacin (10 μM) and 1H-[1,2,4]oxadiazolo-[4,3-a]quinoxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…26) Several flavonoids have been developed as vasodilator drugs, some with and others without an endothelium-dependent vasodilation effect. 18,27) Our previous study reported that oroxylin A, a flavone isolated from the bark of Eucommia ulmoides OLIV. could relax rat thoracic aorta and the effect was endothelium and NO dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26) Several flavonoids have been developed as vasodilator drugs, some with and others without an endothelium-dependent vasodilation effect. 18,27) Our previous study reported that oroxylin A, a flavone isolated from the bark of Eucommia ulmoides OLIV. could relax rat thoracic aorta and the effect was endothelium and NO dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Then the following experiments were done. [15][16][17][18][19][20][21] 1) To investigate the vasodilatory effect of wogonin, NE (1 µM) or KCl (60 mM) was used to contract the aortic rings. Once a stable contraction was achieved, wogonin (0.1-100 µM) was added cumulatively.…”
Section: Reagentsmentioning
confidence: 99%
“…anti-inflammatory, antioxidant [18][19][20][21], anticancer [22,23], muscular metabolismenhancing [24], anti-photoaging [25], phosphodiesterase (PDE)5 inhibitory [26], anti-cardiovascular disease [27], and viral protease inhibitory [28] activities). A large number of studies have investigated the bioactivities of black ginger extract (KPE), which is rich in PMFs [24,[29][30][31][32][33][34][35][36][37].…”
Section: Backgroundsmentioning
confidence: 99%
“…1,2) The rhizomes of this plant are tinged with-dark purple to black, and have traditionally been used for the treatment of hypertension, [3][4][5] allergy, 6) gastrointestinal disorders, 7) and impotence. 8,9) The extract of the rhizomes of K. parviflora and its constituents were revealed to exhibit several pharmacological activities, such as antiplasmoidal, antifungal, 2) antiinflammatory, [10][11][12] α-glucosidase inhibitory, 13) and xanthine oxidase inhibitory 1) activities and cytotoxicity of several tumor cell lines 14,15) as well as effect of P-glycoprotein function 16) and modulation of multi-drug resistance in cancer cells.…”
mentioning
confidence: 99%
“…18) By a previous chemical study on K. parviflora, presence of several methoxyflavones and related phenolic constituents have been revealed. 2,5,6,[10][11][12][13][14][15]17,[19][20][21][22] During the course of our characterization studies on Thai natural medicines, [23][24][25][26][27][28][29][30][31][32] two new phenolic glycosides named kaempferiaosides A (1) and B (2) were isolated from the rhizomes of K. parviflora together with 24 known compounds. This paper deals with the structure elucidation of 1 and 2, as well as hepatoprotective effect of the constituents from the rhizomes of K. parviflora on D-galactosamine (D-GalN)-induced cytotoxicity in primary cultured mouse hepatocytes.…”
mentioning
confidence: 99%